Anthropometric characteristics in Czech elite female gymnasts - Hedbavny, P.; Cacek, J.; Svobodová, L. (Journal of Human Sport & Exercise, 2014)
The aim of this paper is a description of selected parameters of body composition of elite sport gymnasts from the Czech Republic (30th place at 2010 World Championship). Eight Czech representatives (aged 18.4 +3.39) participated in this cross-sectional study realized in 2013. Data were measured according to standard testing protocols. Body height and arm spread via anthropometer (cm), body composition and body weight using 6-frequncy bio impedance (InBody 720), circumference characteristics using band meter. Body height of the researched group was 161.0 cm (+ 5.34), compared to average body height of American Olympic team (2nd in World ranking) was only 153cm in 2008 (+7) (Sands et al. 2012). Body weight of Czech gymnasts was 55.7 kg (+ 5.46), American women gymnasts according to Sandse et al. weighed only 47.5 kg (+5.7). BMI (kg.m-2) was measured 21.35 (+ 1.66) which is a higher value than according to Grasgruber et al (2008) an average value of this parameter in participants of 2003 World Championship finals (18.77 Europeans, 16.73 Asians). Average amount of subcutaneous fat 13.33 % (+2.81) was, on the contrary, lower than stated by Georgopoulos et al. in a study of 113 participants of European and World championships in last 15 years (16.4 %; +4.99). Hip-waist ratio was 0.85 (+0.03). Arm spread, particularly important in gymnastics due to effectiveness of leverage mechanisms, was measured 164.9 cm (+ 6.85), showing relatively long leverages, or above-average shoulder width considering average height of the group 161 cm. Long leverages are beneficial for floor exercise and vault. Overall, compared to World competition, Czech gymnasts show above-average height as well as BMI value. Considering relatively low amount of subcutaneous fat we speculate that compared to elite world competition, Czech gymnasts will show higher relative values of skeletal muscles which may disadvantage them in some aspects of performance.